A structured review of placental morphology and histopathological lesions associated with SARS-CoV-2 infection. (November 2020) - Sharps, Megan C.; Hayes, Dexter J.L.; Lee, Stacey; Zou, Zhiyong; Brady, Chloe A.; Almoghrabi, Yousef; Kerby, Alan; Tamber, Kajal K.; Jones, Carolyn J.; Adams Waldorf, Kristina M.; Heazell, Alexander E.P.
Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel coronavirus, was first identified after a cluster of cases in Wuhan, China in December 2019. Whether vertical transmission or placental pathology might occur following maternal infection during pregnancy remains unknown. This review aimed to summarise all studies that examined the placenta or neonates following infection with SARS-CoV-2, or closely related highly pathogenic coronavirus (SARS-CoV-1, or the Middle East respiratory syndrome coronavirus (MERS-CoV)). Structured literature searches found 50 studies that met the inclusion criteria. Twenty studies reported placental histopathology findings in third trimester placentas following maternal SARS-CoV-2 infection. Using the Amsterdam Consensus criteria to categorise the histopathology results, evidence of both fetal vascular malperfusion (35.3% of cases; 95% Confidence Interval (CI) 27.7–43.0%) and maternal vascular malperfusion (46% of cases; 95% CI 38.0–54.0%) were reported, along with evidence of inflammation in the placentas (villitis 8.7% cases, intervillositis 5.3% of cases, chorioamnionitis 6% of cases). The placental pathologies observed in SARS-CoV-2 were consistent with findings following maternal SARS-CoV-1 infection. Of those tested, a minority of neonates (2%) and placental samples tested positive for SARS-CoV-2 infection (21%). Limited conclusions can be drawn about the effect of maternal SARS-CoV-2 infection on placental pathology as most lack control groups and the majority of reports followed third trimester infection. Collaboration to maximise the number of samples examined will increase the reliability and generalisability of findings. A better understanding of the association between maternal SARS-CoV-2 infection and placental pathology will inform maternity care during the coronavirus pandemic. Highlights: Placental findings following maternal COVID-19, SARS or MERS were reviewed. Minority of infants (2%) and placentas (21%) tested were positive for COVID-19. Fetal and maternal vascular malperfusion were most frequently noted following COVID-19. Minority of placentas demonstrated inflammatory lesions. The association between maternal COVID infection and placental pathology is unclear.